ANALISIS PERAN GURU DALAM MENINGKATKAN KEMAMPUAN BERHITUNG PERMULAAN ANAK AUTISME KELOMPOK B DI TK ANUGERAH - Maria Feronika Simatupang; Suri Handayani Damanik (STKIP Subang, 2026)
Early numeracy skills are part of early childhood cognitive development and serve as a crucial foundation for understanding number concepts and basic mathematics. This study aims to analyze the role of teachers in improving the early numeracy skills of children with autism in Group B at Anugerah Preschool. Using a descriptive qualitative method with a naturalistic approach, this study involved one teacher as the research subject to identify the teacher’s role as an instructor, facilitator, motivator, and administrator. Data collection was conducted comprehensively through direct observation of classroom learning processes, semi-structured interviews with the classroom teacher, and documentation of the curriculum and daily learning assessment results of the children. The results of the study indicate that the teacher has effectively fulfilled her roles through individualized and visual approaches. As instructors and facilitators, teachers utilized number cards in a step-by-step manner (sequencing, identifying, labeling) combined with the repeated demonstration method. As motivators, the teachers provided positive verbal and nonverbal reinforcement to foster the children’s self-confidence. As administrators, the teachers developed intermediate-level curriculum guidelines that were adaptively tailored to the attention span and language abilities of children with autism.